Periapical bone edema volume in 3D MRI is positively correlated with bone architecture changes - Alexander W. Marka; Monika Probst; Tobias Greve; Nicolas Lenhart; Niklas Graf; Florian Probst; Gustav Andreisek; Thomas Frauenfelder; Matthias Folwaczny; Egon Burian (Insights into Imaging)
Abstract Objectives To compare and correlate bone edema volume detected by 3D-short-tau-inversion-recovery (STIR) sequence to osseous decay detected by a T1-based sequence and conventional panoramic radiography (OPT). Materials and methods Patients with clinical evidence of apical periodontitis were included retrospectively and received OPT as well as MRI of the viscerocranium including a 3D-STIR and a 3D-T1 gradient echo sequence. Bone edema was visualized using the 3D-STIR sequence and periapical hard tissue changes were evaluated using the 3D-T1 sequence. Lesions were segmented and volumes were calculated for bone edema and structural decay. OPTs were assessed for corresponding periapical radiolucencies using the periapical index (PAI). Results Of the 42 patients of the initial cohort 21 patients with 38 periapical lesions were included in the analysis (mean age 57.2 ± 13.8 years, 9 women). Reactive bone edema was detected on MRI in 23 periapical lesions with corresponding radiolucency on OPT. Fifteen periapical lesions were detected only in the STIR sequence. The volume of edema measured in the STIR was significantly larger in OPT-positive lesions (mean: STIR (OPT+) 207.3 ± 191.1 mm³) compared to OPT-negative lesions (mean: STIR (OPT−) 29.5 ± 34.2 mm³, p < 0.001). The ROC curve analysis demonstrated that Volume T1 (0.905, p < 0.01) and Volume STIR (0.857, p < 0.01) measurements have strong diagnostic performance for distinguishing OPT-positive from OPT-negative lesions. Conclusion Clinically symptom-free patients without pathologic changes in OPT can show signs of inflammation within the periapical bone. Bone edema volume visualized by STIR sequence exceeds bone architecture changes indicated in T1-based imaging and might precede osteolysis in dental radiography. Critical relevance statement These results show that subtle intraosseous inflammation within the periapical tissue might remain undetected by conventional dental radiography and T1-based sequences. This emphasizes the potential of MRI in secondary prevention in dentistry. Key Points Conventional panoramic radiography (OPT) may show only delayed findings of pathological periapical changes. MRI detected bone edema in 23 radiolucent lesions on OPT. MRI revealed 15 lesions only visible with STIR sequences. STIR sequences showed bone inflammation undetectable by conventional radiography or T1 imaging. MRI offers diagnostic advantages for early dental pathology detection. Graphical Abstract